Specific Nucleotides in the Common Region of the Begomovirus Tomato Rugose Mosaic Virus (ToRMV) Are Responsible for the Negative Interference over Tomato Severe Rugose Virus (ToSRV) in Mixed Infection - Nogueira, Angélica M. [UNESP]; Barbosa, Tarsiane M. C.; Quadros, Ayane F. F.; Orílio, Anelise F.; Bigão, Marcela C. J.; Xavier, César A. D.; Ferro, Camila G.; Zerbini, Francisco Murilo (MDPI, 2023)
Mixed infection between two or more begomoviruses is commonly found in tomato fields and can affect disease outcomes by increasing symptom severity and viral accumulation compared with single infection. Viruses that affect tomato include tomato severe rugose virus (ToSRV) and tomato rugose mosaic virus (ToRMV). Previous work showed that in mixed infection, ToRMV negatively affects the infectivity and accumulation of ToSRV. ToSRV and ToRMV share a high degree of sequence identity, including cis-elements in the common region (CR) and their specific recognition sites (iteron-related domain, IRD) within the Rep gene. Here, we investigated if divergent sites in the CR and IRD are involved in the interaction between these two begomoviruses. ToSRV clones were constructed containing the same nucleotides as ToRMV in the CR (ToSRV-A(ToR:CR)), IRD (ToSRV-A(ToR:IRD)) and in both regions (ToSRV-A(ToR:CR+IRD)). When plants were co-inoculated with ToRMV and ToSRV-A(ToR:IRD), the infectivity and accumulation of ToSRV were negatively affected. In mixed inoculation of ToRMV with ToSRV-A(ToR:CR), high infectivity of both viruses and high DNA accumulation of ToSRV-A(ToR:CR) were observed. A decrease in viral accumulation was observed in plants inoculated with ToSRV-A(ToR:CR+IRD). These results indicate that differences in the CR, but not the IRD, are responsible for the negative interference of ToRMV on ToSRV.
Keywords: begomoviruses; geminiviruses; infectivity; Rep gene; viral replication